Niesymetryczne Rozciąganie Tarczy Osłabionej Szczeliną - Matczyński, M. (Engineering Transactions, 1972)
On the basis of the results of paper [1] the present paper determines the stress intensity factors at the tips of the crack under the assumption that the plane containing the crack is subject to the action of two equal and opposite forces directed along a line perpendicular to the crack. The graphs are given representing the stress intensity factors at the tips of the crack as functions of the distance of the points of application of the forces from one of the tips of the crack.